Montreal Museum of Fine Arts, Collection of Mediterranean Antiquities, Vol. 4: The Coptic Textiles - Fossey, John M.; Caron, Beaudoin (Monumenta Graeca et Romana, 2020)
This catalogue of the Coptic Textiles in the Collection of Mediterranean Antiquities at the Montreal Museum of Fine Arts provides a detailed analysis of 64 textiles from both historical and weaving practice points of view. This approach provides a fuller understanding of the cultural situation in which such textiles were produced and circulated. Dr. Landry's experience of over 40 years of weaving and scholarship highlights the elements of knowledge and skill held and applied by weavers in Antiquity. This perspective complements and expands on the focus on imagery usually provided by art historians regarding textiles of this period. This catalogue shows how much more cultural information can be accessed when the technical, economic, and practical character of both production and use are adequately integrated into the study of material artefacts.